Feasibility of the Suzuki-Miyaura Cross-Coupling on a Model System - Wen-Long, Wei; Xin, Cao; Xing, Li; Hong-Hong, Chang; Xian-Yong, Pang (Asian Journal of Chemistry, 2012)
A density functional theory study at the level of B3LYP/6-311 G (d,p) is carried out on the Suzuki-Miyaura cross-coupling of aryl chlorides and arylboronic acids, in this work. The results on the structure parameters are in good agreement with the experimental findings in some aspects. However, discrepancies still arise in reasonable range. A static analysis of the reactants is obtained through the calculation in order to explain the feasibility of reaction in stereo-hindrance and electronic effect.